A New Mode of MSME Empowerment Creating a Strong Indonesian Economy (Perspective on Business Competition Law) - Asmah, Asmah; Rompegading, Melantik (Journal of Progressive Law and Legal Studies, 2024)
Indonesia is included in the category of world economic power in terms of increasing micro, small and medium enterprises (MSMEs), which amount to 19 million. The business competition law in Indonesia in Law No. 5 of 1999 and the Business Competition Supervisory Commission (KPPU) can make MSMEs an important sector in the Indonesian economy through this institution. MSMEs that carry out business or partner with investors or large businesses reduce unfair business competition that can benefit both parties. However, along with the development of technology and people's habits, business actors, especially the MSME sector, are doing various activities to increase turnover by carrying out various business strategies so that their business can continue. Law No. 20 of 2008 concerning Micro, Small, and Medium Enterprises regulates MSMEs' activities, hoping that MSMEs can realize Indonesia as a world economic power with an empowerment model from upstream to downstream and can be easily recognized and accessed quickly. The research method used is descriptive normative legal research. As a result, the new model of the compass network in empowering MSMEs by accelerating the network, roadmap mode, and images can increase MSME production and be free from the influence of an uncertain economic situation.